Strategi Bisnis Mikro Kecil Menengah Dalam Mempertahankan Usaha Pada Masa Pandemi Covid-19 - Latifah, Nunuk; Widayani, Anna; Wardani, Shanti Ike; Normawati, Rani; Rachmawati, Ika (Politeknik Negeri Madiun, 2021)
The COVID-19 pandemic which is currently sweeping the world, including Indonesia, has an enormous impact on the economic sector. Government policy to encourage people to move at home only affects the consumption pattern of the community. As one of the affected sectors, MSMEs must be able to see this as a challenge as well as an opportunity in marketing their products. The problem experienced by MSMEs is how to maintain their existence by making various efforts, including by conducting various business innovations and strategy innovations. For this reason, it is necessary to have various efforts in developing business strategies that can be carried out to maintain the business. This is the basis for the community service implementation team to hold a Webinar